PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL INTERAKTIF BERBASIS SMARTPHONE PADA MATA KULIAH TEKNIK MENGHIAS KAIN JURUSAN PKK FT UNM - Hasmia; A.Hudiah; Hamidah Suryani (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to discover: 1) the results of the development of Smartphone-based interactive e-modele in Fabric Decorating Techniques Courses to improve the learning outcomes in PKK Department FT UNM, 2) whether the feasibility of the smartphone-based interactive e-modele learning media developed meets valid criteria, 3) whether the feasibility of smartphone-based interactive e-modele learning media developed meets practical criteria, 4) whether the feasibility of the smartphone-based interactive e-modelelearning media developed meets effective criteria. The method used in this study is Research and Development (R&D). The research subjects were 32 students and 2 lecturers in PKK Department FT UNM. Data collection techniques used were tests, questionnaires, and e-modele validation. The module development process employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) e-development model. The analysis phase includes an analysis of the needs for learning resources, curriculum, and materials. The design stage includes creating the e-modele framework, determining the layout and reference book, and preparing the e-modele assessment instrument. The development stage includes e-modele development, expert validation and e-modele revision. The implementation stage is the trial stage of the e-modele, which had been validated and revised for students. The evaluation stage is the stage of analyzing the strengths and weaknesses of the e-modele that had been tested. The quality of the module is determined by three criteria: validity, practicality, and effectiveness. This e-modele is declared as valid based on an assessment from the material expert with an average of 87% (very valid) and an assessment from the media expert with an average of 91% (very valid). Moreover, the e-modele is declared as practical for use by students based on the results of the students’ response questionnaire with an average of 83% (Very practical). Furthermore, based on the test results before and after using the e-modele, it is declared as effective for use by students based on the results of the pretest and p osttest with an average score of 71% (effective).